2017
DOI: 10.2147/ott.s127317
|View full text |Cite
|
Sign up to set email alerts
|

The association between SPINK1 and clinical outcomes in patients with prostate cancer: a systematic review and meta-analysis

Abstract: Evidence of the prognostic role of serine peptidase inhibitor Kazal type 1 (SPINK1) in prostate cancer (PCa) is controversial. The aim of this study was, therefore, to evaluate the association between SPINK1 and clinical outcomes in PCa. Searches were made of PubMed, Medline, Embase, and the China Biology Medicine disc (CBMdisc) up to January 2017. The Newcastle–Ottawa Scale was used to assess the risk of bias of included studies. RevMan software was used to perform meta-analysis, and the Grading of Recommenda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Ida et al [22] demonstrated that SPINK1 stimulates the proliferation of colon cancer cells and is involved in colorectal cancer progression. Moreover, overexpression of SPINK1 is associated with adverse prognosis in other cancers, including prostate cancer [23], hepatocellular cancer [24] and breast cancer [25]. Thus, SPINK1 can be used as a prognostic tumor marker.…”
Section: Discussionmentioning
confidence: 99%
“…Ida et al [22] demonstrated that SPINK1 stimulates the proliferation of colon cancer cells and is involved in colorectal cancer progression. Moreover, overexpression of SPINK1 is associated with adverse prognosis in other cancers, including prostate cancer [23], hepatocellular cancer [24] and breast cancer [25]. Thus, SPINK1 can be used as a prognostic tumor marker.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular studies have led to the characterization in mCRPC patients of a subgroup comprising about 10% of cases with an overexpression of the SPINK1 gene, in association with negativity for ETS fusions [312]. SPINK1 overexpression is associated with a negative prognosis in patients with mCRPC, but not in those with localized disease [347]. The mechanisms responsible for SPINK1 overexpression are unclear, but it evident that it is not related to chromosomal rearrangement, deletion or amplification.…”
Section: Gene Expression Profiling Studiesmentioning
confidence: 99%
“…In prostate cancer, EGFR signaling pathway induces SPINK1 trypsin inhibitor to promote EMT [ 63 ] and overexpression of SPINK1 represents its aggressive form [ 64 ]. Although studies have shown positive association of SPINK1 expression with biochemical recurrence and castration-resistant prostate cancer [ 65 ], there was no significant difference in SPINK1 expression between incidental and metastatic cases [ 66 ]. The positive correlation between SPINK1 and CD82 expression in PrEC-31 normal prostate cells remains unexplained without further studies.…”
Section: Discussionmentioning
confidence: 99%